2018
DOI: 10.1589/jpts.30.207
|View full text |Cite
|
Sign up to set email alerts
|

Immediate effects of a single session of robot-assisted gait training using Hybrid Assistive Limb (HAL) for cerebral palsy

Abstract: [Purpose] Robot-assisted gait training (RAGT) using Hybrid Assistive Limb (HAL, CYBERDYNE) was previously reported beneficial for stroke and spinal cord injury patients. Here, we investigate the immediate effect of a single session of RAGT using HAL on gait function for cerebral palsy (CP) patients. [Subjects and Methods] Twelve patients (average age: 16.2 ± 7.3 years) with CP received a single session of RAGT using HAL. Gait speed, step length, cadence, single-leg support per gait cycle, hip and knee joint an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(52 citation statements)
references
References 44 publications
1
51
0
Order By: Relevance
“…With regard to the immediate effect, gait training using HAL significantly increased the gait speed and mean step length. Matsuda et al compared gait function before and after a HAL intervention for CP patients and found a significantly increased hip extension angle and knee extension angle in the stance phase and knee flexion angle in the swing phase 16 ) . Therefore, we considered that the step length improved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the immediate effect, gait training using HAL significantly increased the gait speed and mean step length. Matsuda et al compared gait function before and after a HAL intervention for CP patients and found a significantly increased hip extension angle and knee extension angle in the stance phase and knee flexion angle in the swing phase 16 ) . Therefore, we considered that the step length improved.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies have reported the effect of gait training using HAL among CP patients. Matsuda et al reported that 12 CP patients who participated in a single gait training session using HAL showed an instantaneous improvement in single-leg support per gait cycle and hip and knee joint angle during walking 16 ) . However, there has been no other report on the immediate effect on walking ability of HAL training in CP patients.…”
Section: Introductionmentioning
confidence: 99%
“…The wearer operates HAL by adjusting his or her own muscle activity. Clinical trials of training using HAL have been already conducted for patients with stroke [ 18 , 19 ], spinal cord injury [ 20 ], cerebral palsy [ 21 ], and neuromuscular diseases [ 22 ], and its clinical safety has been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…It has electrically driven power units at the bilateral hip and knee joints, which are actuated, amplifying the neuro-muscular activation of the relevant lower-limb muscles. HAL is known to be effective for gait improvement after neurological motion impairments including stroke [11,12], myelopathy in acute and chronic phases after spine surgery [13], spinal cord injury [14][15][16][17], and cerebral palsy [18]. However, regardless of these recent reports, improvement of DHS using HAL is reported only for a case so far [10].…”
Section: Introductionmentioning
confidence: 99%